PEMBERDAYAAN UMKM DENGAN MEMPERKUAT PERAN KOPERASI KONSUMEN BATANG SAPONGGOL SEJAHTERA SEBAGAI LEMBAGA KEUANGAN NON BANK DI DESA PERKEBUNAN BATANG SAPONGGOL - Sawaluddin Siregar; Damanik, Agustina (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
This study describes the role of cooperatives in improving the economic welfare of the community, the people's economic system of joint ventures on the principle of kinship. Cooperative Program as a non-bank financial institution. in improving the economic welfare of the Batang Saponggol Sejahtera community, namely fighting for how through economic organizations can develop the economic welfare of the community. This research method uses qualitative research, namely research that describes the facts encountered, while this research approach is qualitative descriptive. The subjects in this study are core management members and additional informants from several Batang Saponggol Plantation village communities. data collection techniques, namely observation, interviews and documentation, validation from using theoretical triangulation techniques and source triangulation;  and data analysis using data collection. The results of this study are 1. The economic development program by the Batang Saponggol Sejahtera Consumer Cooperative in Batang Saponggol Plantation Village, namely savings and loans in the plantation sector, and services (procurement of goods), increasing the human resources of Cooperative members in the plantation sector such as fertilizer processing, so that it can save production costs for its members.  2. The obstacles faced from the internal aspect, namely the limited human resources and inadequate infrastructure, while the external aspect, namely community support, makes the Batang Saponggol Sejahtera Consumer Cooperative as an alternative to improve economic welfare in the Batang Saponggol Plantation Village. 3. Efforts are made to improve the quality of human resources through socialization or training and increase the capital or assets of the Cooperative through government cooperation and to support the livelihood of the members of the Cooperative.